2013
DOI: 10.1016/j.jjcc.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Reference interval of pregnancy-associated plasma protein-A in healthy men and non-pregnant women

Abstract: The reference interval of PAPP-A differed for men and non-pregnant women. In clinical practice, <22.9 ng/mL for men and <33.6 ng/mL for non-pregnant women may be used as reference intervals for PAPP-A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…PAPPA is a metalloprotease belonging to the metzincin superfamily of zinc peptidase (Leguy et al 2014 ). It is an active homodimer (dPAPPA), circulating at very low levels in non-pregnant women and men, and regulates cell differentiation and proliferation by cleaving insulin-like growth factor binding proteins 4 and 5 (D’Elia et al 2012 ; Coskun et al 2013 ). During pregnancy, PAPPA is produced at high levels by the placenta and circulates as a heterotetrameric complex (htPAPPA).…”
Section: Discussionmentioning
confidence: 99%
“…PAPPA is a metalloprotease belonging to the metzincin superfamily of zinc peptidase (Leguy et al 2014 ). It is an active homodimer (dPAPPA), circulating at very low levels in non-pregnant women and men, and regulates cell differentiation and proliferation by cleaving insulin-like growth factor binding proteins 4 and 5 (D’Elia et al 2012 ; Coskun et al 2013 ). During pregnancy, PAPPA is produced at high levels by the placenta and circulates as a heterotetrameric complex (htPAPPA).…”
Section: Discussionmentioning
confidence: 99%
“…These results were however not significant. Coskun et al [15] found median PAPP-A concentration in women (3.40 ng/mL) significantly lower than in men (6.85 ng/mL). When dividing the group of women into pre-and postmenopausal, the median PAPP-A concentrations were 2.60 ng/mL and 8.50 ng/mL respectively -a difference that was not significant.…”
Section: Discussionmentioning
confidence: 96%
“…Samples for measurement of PAPP-A were drawn before the first dose of heparin was given, every 15 min for the first 4½ h, and every 30 min for the following 4 h (i.e. after 15,30,45,60,75,90,105,120,135,150,165,180,195,210,225,240,255,270, 300, 330, 360, 390, 420, and 450 min), giving a total of 25 samples. In addition to serum samples for PAPP-A measurement, we also drew blood for monitoring activated partial thromboplastin time (APTT) at the same time points.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is active as a homodimer (dPAPP-A) which cleaves insulin-like growth factor binding proteins 4 and 5, thus regulating local IGF bioavailability and hence cell differentiation and proliferation [ 3 , 4 ]. dPAPP-A circulates at very low levels in non-pregnant women and men [ 5 ]. This dPAPP-A is abundantly expressed in unstable coronary atherosclerotic plaques and can be released in the event of rupture, thus rendering dPAPP-A a biomarker for coronary syndrome and unstable angina [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%